The Impact of Technology Integration on Student Learning Outcomes: A Comparative Study - Reyaz Ahmad Bhat (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Abstract:This research paper examines the effects of technology integration on student learning outcomes through a comparative study. By analyzing existing literature, empirical data, and case studies, the paper explores the potential benefits and challenges of integrating technology into educational settings and assesses its impact on student achievement and engagement. The study also considers varying approaches to technology integration and their influence on diverse student populations.